Combatting bacterial infections by killing persister cells with mitomycin C. (18th May 2015) - Kwan, Brian W.; Chowdhury, Nityananda; Wood, Thomas K.
Summary: Persister cells are a multi‐drug tolerant subpopulation of bacteria that contribute to chronic and recalcitrant clinical infections such as cystic fibrosis and tuberculosis. Persisters are metabolically dormant, so they are highly tolerant to all traditional antibiotics which are mainly effective against actively growing cells. Here, we show that the FDA‐approved anti‐cancer drug mitomycin C (MMC) eradicates persister cells through a growth‐independent mechanism. MMC is passively transported and bioreductively activated, leading to spontaneous cross‐linking of DNA, which we verify in both active and dormant cells. We find MMC effectively eradicates cells grown in numerous different growth states (e.g. planktonic cultures and highly robust biofilm cultures) in both rich and minimal media. Additionally, MMC is a potent bactericide for a broad range of bacterial persisters, including commensal E scherichia coli  K‐12 as well as pathogenic species of E . coli, S taphylococcus aureus and P seudomonas aeruginosa . We also demonstrate the efficacy of MMC in an animal model and a wound model, substantiating the clinical applicability of MMC against bacterial infections. Therefore, MMC is the first broad‐spectrum compound capable of eliminating persister cells, meriting investigation as a new approach for the treatment of recalcitrant infections.